Linear and Nonlinear Age Trajectories of Language Use: A Laboratory Observation Study of Couples' Conflict Conversations. (30th March 2020) - Luo, Minxia; Neysari, Mona; Schneider, Gerold; Martin, Mike; Demiray, Burcu
Abstract: Objectives: This study investigated linear and nonlinear age effects on language use with speech samples that were representative of naturally occurring conversations. Method: Using a corpus-based approach, we examined couples' conflict conversations in the laboratory. The conversations, from a total of 364 community-dwelling German-speaking heterosexual couples (aged 19–82), were videotaped and transcribed. We examined usage of lower-frequency words, grammatical complexity, and utterance of filled pauses (e.g., äh ["um"]). Results: Multilevel models showed that age effects on the usage of lower-frequency words were nonsignificant. Grammatical complexity increased until middle age (i.e., 54) and then declined. The utterance of filled pauses increased until old age (i.e., 70) and then decreased. Discussion: Results are discussed in relation to cognitive aging research.